Molecular characterisation of Ovine CD1 - Ferguson, Elaine Dorothea (The University of Edinburgh, 1994)
The CD1 molecules are a family of ß2microglobulin- associated glycoproteins with strong structural homology, but weaker sequence homology, to the MHC class I antigens. In contrast to the classical class I antigens, CD1 molecules exhibit restricted tissue expression (cortical thymocytes, dendritic cells, a subset of B cells and some intestinal epithelial cells), and are nonpolymorphic. Five CD1 genes have been identified in humans, two in the mouse and several in other mammalian species (Calabi et al, 1991). CD1 expression has also been detected by immunohistological techniques in the cow, sheep and pig.

The MHC class I -like structure of CD1 and the expression on classical antigen presenting cells of the immune system has pointed to a role for CD1 in antigen presentation. Indeed, evidence has been accumulating over the past few years to support this view, with several reports suggesting that CD4 -8- T cells in particular may be able to recognise nonclassical presentational elements including MHC class lb molecules such as TLa and Qa, as well as CD1. Most recently, CD1b molecules on human monocytes have been demonstrated to restrict the response of CD4 -8- T cells to antigens derived from M. tuberculosis (Porcelli et al, 1992).

Previous studies on the ovine CD1 family have involved the use of monoclonal antibodies to assess tissue expression and distribution, and biochemical analyses of the ovine CD1 antigens. However, no studies have been carried out to investigate ovine CD1 at the molecular level. Therefore, a human CD1 C a3 probe was used to screen several sheep thymocyte cDNA libraries. The HCD1 B -like clone SCD1 A25 was isolated from a foetal thymocyte library. A homologous probe comprising the a3/TM /CYT domains from this clone was derived by PCR amplification and used to identify a further three ovine clones - SCD1 B -42, SCD1 B -52 and SCD1T10. Three of the four clones are truncated at the 5' end, with sequences beginning towards the end of the al domain or the start of the a2 domain. These 5' truncation events probably reflect poor reverse transcriptase activity during library preparation. The fourth clone, SCD1 B -52, represents a transcript containing a precise a3 deletion. The PCR technique was used to amplify the missing 5' ends from two of the three truncated$equences, thus generating full length coding sequence for two of the four ovine CD1's identified.

Comparison of the ovine CD1 sequences amongst themselves has shown them to be 81 -96% identical at the nucleotide level and 79 -90% identical at the amino acid level, suggesting that the four clones represent different gene products rather than allelic variants of CD1. The sheep sequences have also been analysed by comparison to the human, mouse and rabbit coding seqences. Perhaps unexpectedly, given the existence of five different human CD1 genes, all of the ovine CD1 sequences are most homologous to human CD1 B at both the nucleotide and amino acid levels. The sheep CD1 sequences also show a high percentage sequence identity to the cottontail rabbit sequence, which is itself most similar to HCD1 B.

Southern blot analysis of genomic DNA digested with a variety of enzymes and probed with the homologous a3 probe has indicated the possible existence of up to seven ovine CD1 genes. Further studies are required to determine which of these genes are expressed and to identify the genes encoding the CD1 molecules recognised by the monoclonal antibodies. The significance and implications of these results are discussed and potential further experiments suggested.